2020
DOI: 10.3389/fmicb.2020.01065
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Gut Microbiota and Inflammatory Diseases: The Role of Macrophages

Abstract: Gut microbiota, an integral part of the human body, comprise bacteria, fungi, archaea, and protozoa. There is consensus that the disruption of the gut microbiota (termed "gut dysbiosis") is influenced by host genetics, diet, antibiotics, and inflammation, and it is closely linked to the pathogenesis of inflammatory diseases, such as obesity and inflammatory bowel disease (IBD). Macrophages are the key players in the maintenance of tissue homeostasis by eliminating invading pathogens and exhibit extreme plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
155
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(159 citation statements)
references
References 114 publications
3
155
0
1
Order By: Relevance
“…They express pattern recognition molecules, such as Toll-like Receptor (TLR) 4, to recognize foreign pathogens, remove toxic molecules, and protect against infection. The pro-inflammatory endotoxin or lipopolysaccharide (LPS) is produced by Gram-negative microorganisms and binds to TLR4, triggering the inflammation process [ 53 ]. In the present investigation, RAW 264.7 macrophages were stimulated with LPS 0.1 μg/mL to establish pro-inflammatory conditions in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…They express pattern recognition molecules, such as Toll-like Receptor (TLR) 4, to recognize foreign pathogens, remove toxic molecules, and protect against infection. The pro-inflammatory endotoxin or lipopolysaccharide (LPS) is produced by Gram-negative microorganisms and binds to TLR4, triggering the inflammation process [ 53 ]. In the present investigation, RAW 264.7 macrophages were stimulated with LPS 0.1 μg/mL to establish pro-inflammatory conditions in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…This was consistent with another study that indicated the immunoinhibitory properties of Bacteroides LPS, making it less effective in providing early life signals required to maintain mucosal homeostasis (and prevent inflammation) than other forms of LPS [ 101 , 103 ]. Interestingly, it is well known that the balance between the activation or suppression of the M1 or M2 macrophages can either enhance or terminate the auto-immune response in the gut which can be affected by the gut microbiome [ 106 ]. The low-grade intestinal inflammation in individuals with T1D was shown to enhance the polarization of the pancreatic macrophages into the M1 classically activated macrophages [ 107 ], in which the bacterial LPS acts as an activation signal affecting the classically activated M1 macrophages by interacting with its Toll-like receptor 4 (TLR4) receptor and inducing the phosphorylation of both STAT1α and STAT1β [ 108 ].…”
Section: Gut Microbiome Immunity and T1dmentioning
confidence: 99%
“…Furthermore, LPS affects the expression of the inflammatory genes by downregulating the expression of the ( P2Y(2)R ) G-protein-coupled which is necessary for TLR4 phosphorylation in macrophages, mediating the production of the pro-inflammatory cytokines and the type I interferon (IFN) [ 80 ]. These cytokines are involved in organizing the trafficking of autoreactive CD8 + T cells towards the islets which are associated with the initiation of T1D [ 88 , 106 , 108 , 109 , 110 , 111 ]. The dynamic role of the microbiota in modulating the immune system is well known [ 46 , 47 ].…”
Section: Gut Microbiome Immunity and T1dmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity seems to aggravate the burden of inflammatory bowel disease in humans. However, the complex relationship between dysbiosis of gut microbiota and gut inflammation in bowel diseases still needs to be better elucidated in obese humans [11,12]. Dysbiosis is directly related to a higher intestinal permeability due to the epithelial barrier deterioration, increased lipopolysaccharide (LPS) levels in the circulation, small intestine bacterial overgrowth, tight junctions' alteration, and even the whole bacterial translocation, among others, causing endotoxemia, which can reach and damage the liver through the portal vein [13].…”
Section: Introductionmentioning
confidence: 99%